2021
DOI: 10.1101/2021.01.16.426937
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimized CRISPR-mediated gene knock-in reveals FOXP3-independent control of human Treg identity

Abstract: SummaryTreg cell therapy is a promising curative approach for a variety of immune-mediated conditions. CRISPR-based genome editing allows precise insertion of transgenes through homology-directed repair, but use in human Tregs has been limited. We report an optimized protocol for CRISPR-mediated gene knock-in in human Tregs with high-yield expansion. To establish a benchmark of human Treg dysfunction, we targeted the master transcription factor FOXP3 in naive and memory Tregs. Although FOXP3-knockout Tregs upr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 136 publications
(182 reference statements)
0
8
0
Order By: Relevance
“…This possibility is supported by the finding that human fetal naive T‐cells deficient in Helios are unable to differentiate into Tregs in vitro in the absence of TGF‐β [27]. Similarly, our investigation into the role of FOXP3 in mature human Tregs revealed that continuous expression of this master transcription factor is dispensable for maintenance of human Treg identity [21]. Overall, high Helios expression marks stable Tregs whereas Helios mid identifies destabilized Tregs, but Helios expression per se does not have a direct role in maintaining this lineage‐committed state.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…This possibility is supported by the finding that human fetal naive T‐cells deficient in Helios are unable to differentiate into Tregs in vitro in the absence of TGF‐β [27]. Similarly, our investigation into the role of FOXP3 in mature human Tregs revealed that continuous expression of this master transcription factor is dispensable for maintenance of human Treg identity [21]. Overall, high Helios expression marks stable Tregs whereas Helios mid identifies destabilized Tregs, but Helios expression per se does not have a direct role in maintaining this lineage‐committed state.…”
Section: Discussionmentioning
confidence: 70%
“…Treg expansion with CRISPR editing was performed as described previously (Supporting information Fig. S1B) [21]. Cells were preactivated for 5 days with IL-2 and either 1:1 aAPCs or 25 μL/mL CD3/CD28/CD2 tetramer (ImmunoCult Human CD3/CD28/CD2 T Cell Activator, STEMCELL Technologies).…”
Section: Treg Expansion With Crispr Editingmentioning
confidence: 99%
See 2 more Smart Citations
“…In reference to retroviral CAR transfection, lung epithelial-directed Tregs were able to diminish the immune response in a murine airway hyper-reactivity model [169]. The CRISPR-Cas9 method, based on gene knock-in and knock-out, is another that may improve the therapeutic effects of the cells via upregulation of the genes crucial for Tregs [170,171].…”
Section: Conclusion and Future In Tregs Applicationsmentioning
confidence: 99%